An amino-terminal fragment of apolipoprotein E4 leads to behavioral deficits, increased PHF-1 immunoreactivity, and mortality in zebrafish. - Madyson M McCarthy; Makenna J Hardy; Saylor E Leising; Alex M LaFollette; Erica S Stewart; Amelia S Cogan; Tanya Sanghal; Katie Matteo; Jonathon C Reeck; Julia T Oxford; Troy T Rohn (PLoS ONE)
Although the increased risk of developing sporadic Alzheimer's disease (AD) associated with the inheritance of the apolipoprotein E4 (APOE4) allele is well characterized, the molecular underpinnings of how ApoE4 imparts risk remains unknown. Enhanced proteolysis of the ApoE4 protein with a toxic-gain of function has been suggested and a 17 kDa amino-terminal ApoE4 fragment (nApoE41-151) has been identified in post-mortem human AD frontal cortex sections. Recently, we demonstrated in vitro, exogenous treatment of nApoE41-151 in BV2 microglial cells leads to uptake, trafficking to the nucleus and increased expression of genes associated with cell toxicity and inflammation. In the present study, we extend these findings to zebrafish (Danio rerio), an in vivo model system to assess the toxicity of nApoE41-151. Exogenous treatment of nApoE41-151 to 24-hour post-fertilization for 24 hours resulted in significant mortality. In addition, developmental abnormalities were observed following treatment with nApoE41-151 including improper folding of the hindbrain, delay in ear development, deformed yolk sac, enlarged cardiac cavity, and significantly lower heart rates. A similar nApoE31-151 fragment that differs by a single amino acid change (C>R) at position 112 had no effects on these parameters under identical treatment conditions. Decreased presence of pigmentation was noted for both nApoE31-151- and nApoE41-151-treated larvae compared with controls. Behaviorally, touch-evoked responses to stimulus were negatively impacted by treatment with nApoE41-151 but did not reach statistical significance. Additionally, triple-labeling confocal microscopy not only confirmed the nuclear localization of the nApoE41-151 fragment within neuronal populations following exogenous treatment, but also identified the presence of tau pathology, one of the hallmark features of AD. Collectively, these in vivo data demonstrating toxicity as well as sublethal effects on organ and tissue development support a novel pathophysiological function of this AD associated-risk factor.